SMALL AREA ESTIMATION DENGAN METODE PENDEKATAN NONPARAMETRIK KERNEL TERHADAP INDEKS PEMBANGUNAN PEMUDA DI INDONESIA - Syauqi, Irfan; Yanuar, Ferra; Devianto, Dodi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
Youth Development Index (YDI) is a measuring tool for youth development, YDI can describe the progress of youth development at the regional and national levels. This study aims to analyze the YDI model in Indonesia and the factors that influence it using the Small Area Estimation (SAE) method with the Kernel nonparametric approach. This Kernel nonparametric approach is not bound by classical assumptions. The Kernel function approach is based on the approach of using the availability of common variables between censuses and surveys so that it is in accordance with the SAE method which estimates the regression function based on survey information..The data used in this study are secondary data in the form of YDI data in Indonesia obtained from the National Socio-Economic Survey of the Central Statistics Agency (CSA) of Indonesia in 2022 for 34 provinces. In this study, the evaluation of the results of the SAE Kernel method model estimation by calculating the coefficient of determination of 94.56% and the accuracy of the model estimation by finding the Mean Absolute Percentage Error (MAPE) value. Significant factors influencing YDI in Indonesia are the level of youth participation in formal and non-formal education and training.